PENGARUH FAKTOR-FAKTOR EKONOMI TERHADAP KEPATUHAN WAJIB PAJAK (Studi Pada Wajib Pajak Badan di Kota Pekanbaru) - Sahri Romadan; Amir Hasan; Andreas Andreas (PEKBIS, 2019)
This study aims to examine and analyze the effect of economic factors (taxcomplexity, probability detection, tax rate and audit tax) on tax payer compliance. Thepopulation of research is corporate tax payers in Pekanbaru City. There are 150samples, sampling technique is probability sampling, data collection technique withsurvey using a questionnaire. Types of research is quantitative descriptive, usingmultiple regression analysis and moderate regression analysis with satistical programassistance SPSS.17. The results of the reaserch were, The probability of detectionand tax rate affect tax payers compliance. the complexity of taxation and tax audit didnot affect tax payers compliance.